Mitigasi Risiko Pengadaan Bahan Baku di PT Inalum dengan Metode House of Risk (HOR) - Lantana, Muhammad Gesha; Vikaliana, Resista; Kurnia, Gita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
PT Inalum is a company specializing in aluminum production, focusing on smelting business and raw material development into aluminum. Annually, PT Inalum produces approximately 250 thousand tons of aluminum. The procurement of primary raw materials plays a significant role in its production chain. Delay in the delivery of primary raw materials can hinder aluminum production. The aim of this research is to identify the risks that may affect the arrival of primary raw materials at PT Inalum and to develop mitigation strategies to minimize the impact of these risks. The research method used is the House of Risk, consisting of two phases. The first phase involves identifying potential risk events that may affect the arrival of primary raw materials, as well as the involved risk agents. The second phase involves determining the relationship between risk events and risk agents, as well as developing mitigation strategies based on the highest risk ranking. From this research, 35 risk events and 21 risk agents that may affect the arrival of primary raw materials at PT Inalum have been identified. Furthermore, through the analysis of House of Risk phase 2, 7 recommendations for mitigation actions with the highest ranking were obtained, including budget monitoring, inventory management improvement, and enhancement of procurement and logistics procedures. The findings of this research can be implemented in the procurement of primary raw materials at PT Inalum to improve efficiency and reduce the risk of aluminum production delays.